John and Elaine Steinbeck at Swedish Airport - Olle Seijbold:::Creator::::::::::::
John and Elaine Steinbeck being met at Bromma Airport in Stockholm before the Nobel Prize award ceremony. Bo Beskow walks with Elaine, while the permanent secretary of Swedish Academy Anders Osterling walks with John. Original in safe